Pengaruh Rasio Solvabilitas Terhadap Pertumbuhan Laba Pada Sub Sektor Perbankan : (Study Kasus Pada Perbankan BUMN Yang Terdaftar di Bursa Efek Indonesia) - Mulia, Mulia; Munandar, Aris; Alwi, Alwi (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2023)
The purpose of this study is to determine whether there is a simultaneous significant influence between debt to asset ratio (DAR), debt to equity ratio (DER), and time interest earned ratio (TIER) on profit growth in banking companies listed on the IDX. The method in this study is descriptive, with the type of research is associative. The data from this study is secondary data, namely financial statements from state-owned banks listed on the IDX (BTN, Mandiri, BRI, and BNI). The analysis technique in this study is multiple linear regression. The results showed that there was an influence of DAR, and DER on profit growth. The TIER results stated that they did not affect profit growth. Meanwhile, together DAR, DER, and TIER affect profit growth in state-owned banking companies.